Chinese bayberry (Myrica rubra Sieb. et Zucc.) leaves proanthocyanidins inhibit intestinal glucose transport in human Caco-2 cells - Wang, Mengting; Mao, Haiguang; Ke, Zhijian; Chen, Jianchu; Qi, Lili; Wang, Jinbo (Frontiers in Pharmacology, 2024)
Background: The hypoglycemic effects of Chinese bayberry leaves proanthocyanidins (BLPs) have been demonstrated. It is unclear, nevertheless, whether BLPs reduced postprandial blood glucose levels by regulating glucose uptake and glucose transport. Method: This study investigated the effect of BLPs (25, 50 and 100 μg/mL) on glucose uptake and glucose transport in human intestinal epithelial cells (Caco-2 cells). The uptake of 2-Deoxy-2-[(7-nitro-2,1,3-benzoxadiazol-4-yl) amino]-D-glucose (2-NBDG) and disaccharidases activity in Caco-2 cells were measured. The glucose transport ability across the cell membrane was determined using the established Caco-2 monolayer model. The transcript and protein levels of key glucose transporters were analyzed using real-time quantitative polymerase chain reaction (RT-qPCR) and western blotting, respectively. Results: The results showed that BLPs significantly decreased glucose uptake and disaccharidases activity (p<0.05). Otherwise, BLPs treatment obviously inhibited glucose transport across the Caco-2 monolayer in both simulated-fast (5 mM glucose) and simulated-fed (25 mM glucose) conditions. It was attributed to the suppression of glucose transporter2 (GLUT2) and sodium-dependent glucose cotransporter 1 (SGLT1) by BLPs. BLPs were found to significantly downregulated the transcript level and protein expression of glucose transporters (p<0.05). Meanwhile, the mRNA expression of phospholipase C (PLC) and protein kinase C (PKC) involved in the signaling pathway associated with glucose transport were decreased by BLPs. Conclusion: These results suggested that BLPs inhibited intestinal glucose transport via inhibiting the expression of glucose transporters. It indicated that BLPs could be potentially used as a functional food in the diet to modulate postprandial hyperglycemia.